LIBERICA COFFEE SUPPLY CHAIN PERFORMANCE IN KAYONG UTARA DISTRICT - Nadia Hilma; Maswadi Maswadi; Novira Kusrini (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
Coffee is one of Indonesia's export commodities which is quite important as a foreign exchange earner of the country. Coffee production in North Kayong Regency is quite high with the fourth highest position. The priority of supply chain performance is related to the production and distribution process of Liberica coffee products. Therefore, this research was conducted to determine the very important priorities in assessing the performance indicators of the Liberica coffee supply chain in North Kayong Regency in order to carry out improvement or handling efforts in order to meet the objectives of the supply chain. The method used in this study is a descriptive method with qualitative and quantitative data.This research combines the Supply Chain Operation Reference (SCOR) model approach with the Fuzzy-Analytical Hierarchy Process (F-AHP) method. The results shows that the main priority on the performance indicators of the Liberica coffee supply chain in North Kayong Regency at the farmer level for level 1 is SOURCE with a weight of 0.233, level 2 is Reliability with a weight of 0.312, and level 3 is orders customers are sent on time (OCT) with a weight of 0.242. While the main priority at the merchant level for level 1 is PLAN with a weight of 0.313, level 2 is Responsiveness with a weight of 0.245, and level 3 is packaging time (PkT) with a weight of 0.286. Implications of this research is the improve the availability and quality of liberica coffee products better, to reduce delays in meeting customer demands.